Design of Chewing Robot with Less Degrees of Freedom based on Chewing Characteristic - Xuqi Wu-Fan; Qiang Xu; Sheng Liu; Mingming Gu (Jixie chuandong)
Chewing robot is a kind of robot which can simulate human chewing behavior. Most of the existing chewing robots are 6-DOF parallel mechanisms, but the six-degree-of-freedom parallel mechanism has complex structure, high manufacturing cost and difficult control. In view of this situation, the 3-UPS/RPP parallel mechanism is used as the prototype to design a kind of low freedom parallel chewing robot based on the characteristics that human chewing movement can be divided into two stages of chopping and grinding. Then the CAD model is established in the 3D modeling software UG, and related kinematics analysis is carried out. Subsequently, the motion simulation of chopping and grinding is carried out in the virtual prototype analysis software Adams. The results show that the chewing robot can simulate the human chewing performance.